2013
DOI: 10.1007/s10103-013-1405-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of LED-mediated-photobiomodulation therapy on orthodontic tooth movement and root resorption in rats

Abstract: The aim of this experimental study was to evaluate the effects of light-emitting diode-mediated-photobiomodulation therapy (LPT), on the rate of orthodontic tooth movement (TM) and orthodontically induced root resorption, in rats. Twenty male 12-week-old Wistar rats were separated into two groups (control and LPT) and 50 cN of force was applied between maxillary left molar and incisor with a coil spring. In the treatment group, LPT was applied with an energy density of 20 mW/cm(2) over a period of 10 consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 39 publications
0
36
0
12
Order By: Relevance
“…5 Torque force induces bucco-lingual rotation of the tooth, 6 and it has been identified as one of the major risk factors for OIRR. [7][8][9][10] Several studies explored potential treatments for OIIRR [11][12][13][14] but the only reported clinically acceptable modality is low-intensity pulsed ultrasound (LIPUS). 15 LIPUS is acoustic pressure waves that can stimulate a variety of cells including cementoblasts, 16 odontoblasts, 17 osteoblasts, 18 chondrocytes, 19 gingival cells, 20,21 and periodontal ligament cells.…”
Section: Introductionmentioning
confidence: 99%
“…5 Torque force induces bucco-lingual rotation of the tooth, 6 and it has been identified as one of the major risk factors for OIRR. [7][8][9][10] Several studies explored potential treatments for OIIRR [11][12][13][14] but the only reported clinically acceptable modality is low-intensity pulsed ultrasound (LIPUS). 15 LIPUS is acoustic pressure waves that can stimulate a variety of cells including cementoblasts, 16 odontoblasts, 17 osteoblasts, 18 chondrocytes, 19 gingival cells, 20,21 and periodontal ligament cells.…”
Section: Introductionmentioning
confidence: 99%
“…This process results in beneficial therapeutic outcomes including but not limited to the alleviation of pain or inflammation, immunomodulation, and promotion of wound healing and tissue regeneration.^ [1]. PBM therapy was found to have multiple clinical benefits, which includes reducing pain [2][3][4][5][6][7], improving wound healing [8][9][10][11], accelerating bone healing [12][13][14][15][16][17], promoting osteointegration [18], facilitating orthodontic tooth movement [19][20][21][22][23][24][25][26], stimulating bone formation [27][28][29][30][31], and improving periodontal tissue repair and decreasing inflammation and root resorption [23,26,32]. The light sources were laser or a light-emitting diode (LED).…”
Section: Introductionmentioning
confidence: 99%
“…As investigações com LED também elegeram diferentes energias (Ekizer et al, 2015;Fonseca et al, 2013). O emprego de parâmetros distintos é decorrente da busca de uma dose ideal, para um efeito positivo da luz sob os tecidos envolvidos na movimentação ortodôntica.…”
Section: Discussionunclassified
“…(Seifi et al, 2007;Gama et al, 2010;Marquezan et al, 2010;Altan et al, 2012;Seifi et al, 2014). Os achados sobre a quantidade de reabsorção radicular também mostraram resultados conflitantes; alguns autores afirmam que a luz infravermelha diminui a reabsorção radicular (Fonseca et al, 2013;Seifi et al, 2014;Ekizer et al, 2015) enquanto outros autores não encontraram diferença entre os grupos. (Marquezan et al, 2013).…”
Section: Introductionunclassified
See 1 more Smart Citation